THE ANALYSIS OF THE INCIDENTS OF ELECTORAL MALPRACTICES IN THE 2023 PRESIDENTIAL ELECTION IN OYO STATE - CLEMENT C. MBAH; AGARY NWOKOYE; IKWUOMA SUNDAY UDOCHUKWU; OJO AKINWUNMI IDOWU (International Studies Journal)
Conducted amidst notable electoral reforms and technological advancements especially the Electoral Act 2022 and the Bimodal Voter Accreditation System (BVAS) the 2023 presidential election in Oyo State, Nigeria, though improved, was tainted by rampant electoral frauds involving vote buying, ballot box theft, voter intimidation, and technological malfunctions.  This paper investigates the nature and forms of these malpractices, evaluates how well electoral reforms serve to regulate them, and studies their influence on voter confidence, participation, and the legal validity and acceptability of the election result.  Using Institutional Theory, the paper looks at how institutional shortcomings drove ongoing electoral fraud by means of a qualitative research approach based on secondary sources including reports, media analysis, and academic publications.  The findings indicate that while legal and technological innovations were commendable, their implementation was affected by systemic inefficiencies, inadequate training, and poor enforcement strategies.   The study concludes with recommendations intended to enhance electoral integrity, institutional responsibility, and democratic government in Nigeria.